Avaliação histomorfométrica do efeito de diferentes temperaturas de síntese na resposta biológica de hidroxiapatitas carbonatas nanoestruturadas contendo alginato de sódio em defeitos críticos de calvárias de ratos - Uzeda, Marcelo José Pinheiro Guedes de (2014)
Because of its bioactivity and biosorption capacity, non-ceramic carbonated hydroxyapatite containing calcium alginate (cHA) has been recommended as an alternative bone substitute to ceramic hydroxyapatite. In order to establish the best synthesis temperature, this study evaluated the biological response to non-ceramics cHAs synthesized under three different temperatures: 5°C, 37°C and 90°C, compared to ceramic hydroxyapatite (HA) in critical defects of rat calvaria. 72 Wistar rats were divided into 4 groups of 18 individuals for each biomaterial and 6 individuals were used per experimental period of 30, 90 and 180 days. Critical size defects were produced in rat calvaria and filled with various biomaterials. After the respective experimental period, the animals were euthanized to obtain samples. The samples were cleaved and each half was processed for embedded in paraffin and resin. Decalcified samples, fixed in formaldehyde and embedded in paraffin, were stained with HE and histologically analyzed and subjected to histomorphometric assessment with Kruskal-Wallis test (p < 0.05) for comparison between experimental periods. Non-decalcified samples, fixed in alcoholic solution and embedded in resin, were analyzed by polarized light microscopy. The results showed that the synthesis temperature influences the material biosorption capacity and its osteoconductive ability. The Kruskal-Wallis test showed significant difference for groups cHA 5° C and 90° C between 30 and 180 days in amount of new bone formation (p <0.05). The variance analysis showed significant difference between the groups regarding the material biosorption (p < 0.05). In one animal in the group cHA 5ºC 180 days, there was complete closure of the critical size defect by new bone. We conclude that, among all biomaterials compared, cHA 37°C showed the highest biosorption capacity while cHA 5°C , less crystalline, led to the largest amount of newly formed bone.